Effects of communal conflict on enrollment, attendance and achievement of primary school pupils in Rivers State (2015)
Insecurity is a factor that has potency, capable of affecting various activities and engagements in a community or nation adversely. Enrolment, attendance and learning outcomes in schools, located in the areas ravaged by communal conflicts are not equally exempted. This study therefore, investigated the effects of communal conflict on enrollment, attendance, and achievement of primary school pupils in Rivers State. This study adopted a non-experimental research design of the causal comparative type. Stratified random sampling technique was used to select 10 conflict affected and 10 non-affected primary schools in Rivers State. Then 200 primary five pupils and 10 teachers and 10 head teachers from each stratum making a total of 440 subjects in all. School Record Sheet, English language(r=.88) and Mathematics(r=.84) Achievement Tests were used for data collection. Both Descriptive and Inferential Statistics were adopted for data analysis. The findings revealed that total enrolment in the affected schools dwindled, attendance reduced drastically and educational facilities were grossly unavailable in the conflict affected area. Unaffected schools experienced increased enrolment and attendance yearly during the four years under study. There was significant difference in the academic achievement t(324, 025)= 7.198, p< 0.05 between the affected and unaffected primary schools. It was recommended that educative approach should be employed by grassroot government in the state to enhance peaceful coexistence. This will provide enabling environment for schooling of the young ones. Non-Governmental Organizations as well as media should also direct significant effort towards educating communities on effect of conflict.